Thinking without speaking: Neuropsychological testing with individuals who have communication impairments. Issue 7 (9th August 2022) - Malhi, Simritpal Kaur; Welch-West, Penny; Koo, Anna Maria; Fogarty, Jennifer; Lazosky, Andrea
ABSTRACT: Cognitive ability may be masked by communication impairments. This study aimed to assess cognitive functioning using binary choice (i.e., yes/no) neuropsychological tests in patients with communication impairments. Four participants underwent neuropsychological testing. Two participants were in the minimally conscious state (MCS), one participant had locked-in syndrome and was an alternative communication user, and one participant was an augmentative communication user. There was better performance in all cognitive domains for the augmentative and alternative communication (AAC) users (who performed like the non-communication impaired normative data) compared to the MCS participants. However, using established yes/no communication methods, MCS participants performed above chance on a measure of memory and performance on measures of auditory comprehension was variable. Auditory comprehension appeared to be more influenced by working memory demands for the MCS participants than for the AAC users. For emotional functioning, the AAC users endorsed lower mood compared to the MCS participants. The results support the need to assess cognition, communication, as well as capacity in individuals with communication impairments with the consultation of a neuropsychologist and a speech-language pathologist.